Can Tax Incentives Bring Brains Back? Returnees Tax Schemes and High-Skilled Migration in Italy - Jacopo Bassetto; Giuseppe Ippedico (Center for Economic Studies and ifo Institute (CESifo), 2023)
Brain drain is a growing concern for many countries experiencing large emigration rates of their highly educated citizens. While several European countries have designed preferential tax schemes to attract high-skilled individuals, there is limited empirical evidence on the effectiveness of fiscal incentives in a context of brain drain, and on migration responses beyond top earners. In this paper we investigate the effects of the Italian 2010 tax scheme "Controesodo", which granted a generous income tax exemption to young high-skilled expatriates who relocate to Italy. Eligibility requires a college degree as well as being born in 1969 or later, which creates suitable quasi-experimental conditions to identify the effect of tax incentives. Using a Triple Difference design and administrative data on return migration, we find that eligible individuals are 27% more likely to move back to Italy post-reform. Additionally, using social security data from the main origin country of Italian returnees (Germany), we uncover significant effects throughout the wage distribution, suggesting that mobility in response to tax incentives is a broad phenomenon not limited to top earners. A cost-benefit analysis reveals that the direct fiscal impact of the reform – a lower bound of the total effect in the presence of human capital externalities – is marginally positive, by virtue of the tax scheme targeting young high-skilled individuals.
Keywords: J60; H20; F22; 330; Brain Drain; Steuervergünstigung; Einkommensteuer; Rückwanderung; Italien